Testicular orphan nuclear receptor 4 is associated with the radio‐sensitivity of prostate cancer. Issue 14 (14th July 2015) - Yu, Shicheng; Wang, Mingchao; Ding, Xianfan; Xia, Liqun; Chen, Bide; Chen, Yicheng; Zhang, Zhigen; Niu, Yuanjie; Li, Gonghui; Chang, Chawnshang
<x xml:space="preserve">Abstract</x> BACKGROUND It is well known that a significant number of prostate cancers (PCa) showed different extents of radio‐resistance and the tumor may recur after treatment. Recent studies demonstrated that Testicular orphan nuclear receptor 4 (TR4) could play a critical role in anti‐oxidative stress responses and might modulate the DNA damage repair. The objective of this study is to investigate the role of TR4 in the radiotherapy for PCa. METHODS The TR4 expression in tissue samples from PCa patients treated with brachytherapy was measured by immunohistochemistry (IHC). Cell survival test and colony formation assay were applied to test the radio‐sensitivity of PCa cells with modulated TR4 gene expression upon irradiation. RESULTS PCa patients with biochemical recurrence (BCR) after brachytherapy tend to have higher TR4 expression (80%, n = 30) as compared to those without BCR (36.67%, n = 30). Survival analysis demonstrated a significant higher BCR occurrence in patients with high level of TR4 expression (HR = 3.474, 95%CI 1.678–7.192, P = 0.0008). Multivariate analysis showed that the TR4 staining score on IHC was the only significant variable for predicting the PCa patients' clinical outcomes after radiotherapy (OR = 9.919, 95% CI 2.516–39.101, P = 0.001). Using cell survival test and colony forming assay, we found that the addition of functional TR4 in PC3 cells lead to elevated radio‐resistance. In contrast, knocking‐down TR4 in LNCaP cells resulted in increased radio‐sensitivity. The γH2AX foci kinetic analysis suggested that knocking down TR4 might delay the PCa cell's DNA damage repair which would enhance the radio‐sensitivity. CONCLUSION TR4 could mediate the PCa cells' radio‐sensitivity and might become a prognostic indicator for PCa patients received radiotherapy. This study provides a novel approach to manipulate radio‐sensitivity of PCa cells, and may bring a promoted therapeutic outcome of radiotherapy to battle PCa in future. Prostate 75:1632–1642, 2015. © 2015 Wiley Periodicals, Inc.